1993
DOI: 10.1007/bf00195301
|View full text |Cite
|
Sign up to set email alerts
|

Generation process of growth stresses in cell walls: Relation between longitudinal released strain and chemical composition

Abstract: To advance the discussion on the evolution mechanism of tree growth stresses, the relation between released strain and the chemical components was investigated experimentally. The expansive released strain in the longitudinal direction assumed large values as the lignin content increased in the compression wood, but there was no relation between released strain and lignin content in the normal wood region. The contractive released strain assumed large values as the cellulose content and its crystallinity incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 4 publications
(2 reference statements)
1
32
0
Order By: Relevance
“…In Liriodendron tulipifera, the cellulose content increases and the MFA parallels the fiber axis in the tension wood region in the upper side of an inclined stem [10,13]. These changes generate a larger tensile growth stress [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Liriodendron tulipifera, the cellulose content increases and the MFA parallels the fiber axis in the tension wood region in the upper side of an inclined stem [10,13]. These changes generate a larger tensile growth stress [14].…”
Section: Discussionmentioning
confidence: 99%
“…In tension wood, the tensile growth stress increases with the number of gelatinous fibers, increasing cellulose content, and decreasing microfibrillar angle [8,10]. In dicotyledonous trees that lack definite gelatinous fibers, the tensile growth stress increases with cellulose content and decreasing microfibrillar angle and lignin content [8,10]. In trees where the reaction wood is not characterized anatomically, growth stress is used to determine the intensity of the reaction wood [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…In compression wood, both lignin content and microfibril angle (MFA) in the middle layer of the secondary wall (S2) are larger than in normal wood [24,[39][40][41]. In contrast to the tensile L stress generated in normal wood, a compressive L stress, expressed by an expansive L strain, is observed in compression wood; it becomes larger with the increase of MFA.…”
Section: Compression Woodmentioning
confidence: 99%
“…A relationship between growth stress and microfibril angle of secondary wall in wood fibers has been reported in reaction wood in angiosperms: the microfibril angle was smaller in the S2 layers of reaction wood fibers compared to that of opposite wood fibers ( [15,[40][41][42]50]. Okuyama et al [15] suggested that microfibril angle is an important factor in the generation of growth stress in tension wood.…”
Section: Microfibril Angle In Tension Wood Fibermentioning
confidence: 99%
“…2B, 3B) [33][34][35][36][37][38]. In some species having no G-layer in reaction wood, it has been reported that microfibril angle of S2 layer decreased [15,[39][40][41][42] reported that the microfibril angle of S2 layer was very small (5 to 10 degrees) in reaction wood of Magnolia acuminate and Liriodendron tulipifera. In Magnolia obovata and M. kobus, the innermost surface of S2 layer of fiber tracheid wall also showed a small microfibril angle [41].…”
Section: Microfibril Angle In Tension Wood Fibermentioning
confidence: 99%